Lipoprotein Apheresis and Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors in Patients With Heterozygous Familial Hypercholesterolemia: A One Center Study. (January 2021) - Kolovou, Vana; Katsiki, Niki; Makrygiannis, Stamatis; Mavrogieni, Sophie; Karampetsou, Nikoletta; Manolis, Athanasios; Melidonis, Andreas; Mikhailidis, Dimitri P.; Kolovou, Genovefa D.
Aim: We evaluated the lipid-lowering (LL) effect of proprotein convertase subtilisin/kexin type 9 inhibitors (PCSK9i) in patients with heterozygous familial hypercholesterolemia (HeFH) treated with LL-drugs and lipoprotein apheresis (LA). Patients and Methods: The PCSK9i treatment (evolocumab 420 mg/4 weeks, alirocumab 150 mg/2 weeks, or alirocumab 75 mg/2 weeks: 9, 6, and 2 patients, respectively) was initiated in patients with HeFH (n = 17; aged 35-69 years, 10 men, previously treated with statins + ezetimibe ± colesevelam and LA sessions for 2-12 years). A lipid profile was obtained before and immediately after the LA session and before, 1 and 2 months after switching to PCSK9i treatment. The duration of PCSK9i therapy ranged from 3 to 18 months. Results: Median total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) levels before LA were 268, 198, 46, and 126 mg/dL, respectively, and decreased (at the end of the LA session) to 117, 50, 40, and 51 mg/dL, respectively ( P < .001 for TC and P = .001 for all other comparisons). The median time-averaged LDL-C levels following LA were 155 (121, 176; median [25th, 75th percentile]) mg/dL. Median TC, LDL-C, and TG levels before PCSK9i therapy were 269, 190, and 127 mg/dL and decreased to 152, 100, and 95 mg/dL, respectively ( P = .002, P < .002, and P < .03, respectively). Steady LDL-C levels with PCSK9i treatment were significantly lower compared with time-averaged LDL-C levels following LA (median value: 100 vs 155 mg/dL; P = .008). With PCSK9i, from 13 patients with CHD, 6 (46.1%) patients achieved LDL-C <70 mg/dL, and 2 patients (15.4%) achieved LDL-C <100 mg/dL. Lipoprotein apheresis was discontinued in all patients except for 2 who continued once monthly. Conclusions: PCSK9i can reduce LDL-C more consistently over time compared with a transient decrease following LA in HeFH patients. PCSK9i therapy may reduce the frequency of LA. Larger trials are required to establish the clinical implications of PCSK9i in patients previously on LA.